PANCASILA VALUES IN THE LARUNG SESAJI TRADITION IN TAMBAKREJO VILLAGE, WONOTIRTO DISTRICT, BLITAR DISTRICT - Erawanto, Udin; Triantoro, Miranu (JOSAR (Journal of Students Academic Research), 2024)
Abstract The aim of the research was to explore information about the Pancasila values ​​contained in the larung sesaji in Tambakrejo, including vital, material and spiritual values. In determining sources, purposive sampling techniques were used. To obtain information using in-depth interview techniques, observation and documentation. Data analysis uses the Milles and Huberman model. Research results: the tradition of larung sesaji in Tambakrejo Village has: 1) material value, to meet the physical needs of community members eating three times a day in the form of rice, vegetables and side dishes 2) vital value, in the form of equipment used by fishermen such as boats, nets, hooks, flashlights, sarongs, jackets, scales, barrels where fish are caught. 3) spiritual values, there is a prayer event to express gratitude, pray for protection from all dangers and disasters, and pray for the spirits of deceased ancestors. The values ​​of Pancasila are also found in the tradition of celebrating larung sesaji, such as: The first principle of Pancasila, namely the religious behavior of believing in the Almighty God and living in harmony between fellow believers. The value of the second principle of Pancasila is reflected in the social behavior of sharing good fortune, acting fairly, respecting each other, and helping people in need. The third principle of Pancasila is to unite, work together to prepare events and contribute morally, energy, thoughts and materials. The value of the fourth principle of Pancasila is the habit of deliberation (rembug deso), respecting and implementing the results of joint decisions for the smoothness and success of the event. The value of the fifth principle of Pancasila, all those present at the event are treated equally, there is no discrimination, they are aware of their rights and obligations to make the event a success. Keywords: Values, Pancasila, Larung Sesaji